Oddity [videorecording (DVD)] - McCarthy, Damian (Filmmaker); Lee, Gwilym, 1983-; Bracken, Carolyn (Actor); Murphy, Tadhg; Menton, Caroline; French, Jonathan (Actor); Wall, Steve (Actor) (Shudder, 2024)
After Dani is brutally murdered, her blind occultist twin sister Darcy, goes after those responsible using inherited haunted items as her tools of revenge.